BIOLOGI Moduza procris CRAMER (LEPIDOPTERA: NYMPHALIDAE) PADA JABON MERAH (Anthocephalus macrophyllus) - Martini Wali; Noor Farikhah Haneda; Nina Maryana (Universitas Teuku Umar, 2018)
Red jabon (Anthocephalus macrophyllus Roxb. Havil) includes in the familyRubiaceae. This plant has many advantages. This plant is also widely cultivate in plantations industry and plantations community forest today. Moduza procris is a new pests that attacks jabon leaves. The leaf are consumed from the edge and leave the venation. This study aimedto observe biology aspects of M. procris on red jabon. The result showed that life cycle of M. procris was about 25.3 days (larvae stadium was 17.2 days, and pupae 8.1 days). M. proris has 5 instars larvae. The average body size of M. procris was at eggs stadium was 1.32 mm. Size of the larvaes were 7.20, 9.70, 15.60, 24.20 dan 33.90 mm respectively, while the head of larvae were 0.91, 1.92, 2.91, 3.91, and 4.91 mm. Width and length of female pupae was 9.63 mm and 29.63 mm, male pupae was 27.50 mm and 8.00 mm. The body length of adult female was 20.50 mm and male was 16.50 mm, while the wings span of adult female was 67.25 mm and males was 55.00 mm. Keywords: Anthocephalus macrophyllus, Lepidoptera, life cycle, Moduza procris